Red Blood Cell Distribution Width in Hospitalized COVID-19 Patients - Ramachandran, Preethi; Gajendran, Mahesh; Perisetti, Abhilash; Elkholy, Karim Osama; Chakraborti, Abhishek; Lippi, Giuseppe; Goyal, Hemant (Frontiers in Medicine, 2022)
Introduction: Coronavirus disease-2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is causing dramatic morbidity and mortality worldwide. The Red Blood Cell Distribution Width (RDW) has been strongly associated with increased morbidity and mortality in multiple diseases. Objective: To assess if elevated RDW is associated with unfavorable outcomes in hospitalized COVID-19. Methods: We retrospectively studied clinical outcomes of hospitalized COVID-19 patients for their RDW values. In-hospital mortality was defined as primary outcome, while septic shock, need for mechanical ventilation, and length of stay (LOS) were secondary outcomes. Results- A total of 294 COVID-19 patients were finally studied. Overall prevalence of increased RDW was 49.7% (146/294). RDW was associated with increased risk of in-hospital mortality (aOR, 4.5; 95%CI, 1.4-14.3) and septic shock (aOR, 4.6; 95%CI, 1.4-15.1) after adjusting for anemia, ferritin, and lactate. The association remained unchanged even after adjusting for other clinical confounders such as age, sex, body mass index, coronary artery disease, hypertension, diabetes mellitus, and chronic obstructive pulmonary disease. No association was found instead with mechanical ventilation and median LOS. Conclusion: Elevated RDW in hospitalized COVID-19 patients is associated with a significantly increased risk of mortality and septic shock.